The Effectiveness of Using Social Media in the Learning Process - Amare Manfredo (Jayapangus Press, 2023)
Social media has become a tendency among young people nowadays, as well as a learning activity, especially during the pandemic. Social media has become the means of communication in online learning used by educators in the learning process. The research purpose of this study is to describe the kinds of social media and their application, as well as the effectiveness of using social media as a means of communication in online learning. The method used in this research is qualitative descriptive Collecting data; the method used were observation, interview, and closed questionnaire using Google form. The result shows that the social media used in online learning are WhatsApp and Google Forms, WhatsApp is used as written communication to share teaching materials, and Google Form is used to fill the current lists for midterm and final exams. This research concludes that those three social media, WhatsApp and Google Forms, can be used as a means of communication for online learning, yet very effective during the pandemic time nowadays, so the teaching-learning process can still be implemented.